A 25-year-old Woman with Cholecystolithiasis, Cholecystitis, Choledocholithiasis, and Acute Hepatitis - Naldo Nathanael; Hery Djagat Purnomo; Cecilia Oktaria Permatadewi (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Introduction: Gallstone disease stands as the foremost gastrointestinal issue leading to hospital admissions, while also emerging as a substantial global public health concern, impacting approximately one-fifth of the population. Case Report: A 25-year-old woman was admitted with abdominal pain with a history of gallstones. She had risk factors such as obesity with a Body Mass Index (BMI) of  35.3 and dyslipidemia. Further examination showed that she had acute hepatitis and choledocholithiasis. The patient underwent Endoscopic Retrograde Cholangiopancreatography (ERCP) with balloon extraction. The patient recovered from her condition then scheduled for cholecystectomy. Conclusion: This case showed a relatively young female with cholecystolithiasis, cholecystitis,  choledocholithiasis, and acute hepatitis presenting with colicky pain. Comprehensive management of gallstone diseases is essential to avert additional complications and the possibility of relapse, especially considering the young age of the patient.